Legal Issues in Entrepreneurship: Between Regulation, Innovation, And Business Sustainability - Ade Yusdira; Mumuh Mulyana; Mashadi Mashadi; Narrong Hassanee; Sulistiono Sulistiono (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Entrepreneurship plays a pivotal role in fostering economic growth, job creation, and social innovation. However, its development remains inseparable from complex legal challenges. Regulations often serve an ambivalent role: they provide legitimacy and protection, yet at the same time may hinder entrepreneurship through excessive bureaucracy and high compliance costs. This article seeks to examine the key legal issues in entrepreneurship, explore the nexus between regulation, innovation, and sustainability, and propose conceptual recommendations for developing an adaptive and inclusive entrepreneurial ecosystem. Employing a normative–conceptual approach, the study draws upon secondary sources including national regulations, recent international scholarly publications, and institutional reports from the OECD, UNCTAD, and the World Bank. Comparative and thematic analyses were undertaken to map legal issues, assess their implications for innovation, and evaluate their impact on business sustainability. The findings highlight six major legal domains: licensing and bureaucracy, intellectual property rights, business contracts, taxation, labor regulations, and digital and e-commerce law. Regulations are shown to act dually as both enablers and barriers to entrepreneurial innovation. Cross-country evidence further illustrates that developed economies tend to design more adaptive legal frameworks, while developing countries continue to face significant regulatory implementation challenges. In Indonesia, reforms such as the Online Single Submission system, the Omnibus Law on Job Creation, and the Personal Data Protection Law represent important steps forward, yet remain in a transitional stage. The article contributes theoretically by integrating Institutional Theory, Innovation Theory, and the Triple Bottom Line, and provides practical recommendations emphasizing regulatory simplification, stronger intellectual property protection, adaptive digital and green regulations, and greater international policy harmonization   Keywords: Entrepreneurship; Legal Framework; Innovation; Sustainability; Regulatory Reform.